Endothelial dysfunction in autoimmune, pulmonary, and kidney systems, and exercise tolerance following SARS-CoV-2 infection - Sen, Sabyasachi; Khosla, Shikha; Awan, Omar; Cohen, Scott; Gollie, Jared M. (Frontiers in Medicine, 2023)
Long COVID is characterized by persistent symptoms beyond 3-months of severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2) infection that last for at least 2 months and cannot be explained by an alternative diagnosis. Autonomic, immunologic, endothelial, and hypercoagulation are implicated as possible mechanisms of long COVID symptoms. Despite recognition of the public health challenges posed by long COVID, the current understanding of the pathophysiological underpinnings is still evolving. In this narrative review, we explore the long-term effects of SARS-CoV-2 infection on T cell activation such as autoimmune disorders and endothelial cell dysfunction involving vascular impairments within pulmonary and renal architecture. We have described how endothelial dysfunction and vascular abnormalities may underscore findings of exercise intolerance by way of impaired peripheral oxygen extraction in individuals with long COVID.